Respostas

  • PeH
  • Ambicioso
2013-08-06T11:15:05-03:00
(2x - 8) \ (2 - x) > 0 \\ 4x - 2x^2 - 16 + 8x > 0 \\ -2x^2 + 12x - 16 > 0 \\\\\ -2x^2 + 12x - 16 = 0 \\\\ \bullet a = -2 \\ \bullet b = 12 \\ \bullet c = -16 \\\\ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \\\\ x = \frac{-12 \pm \sqrt{12^2 - 4 \cdot (-2) \cdot (-16)}}{2 \cdot (-2)} \\\\ x = \frac{-12 \pm 4}{-4} \rightarrow x' = 2 \ e \ x'' = 4

\bullet \ \text{Estudo de sinal:} \\\\ \begin{cases} \text{Se} \ x < 2 \ ou \ x > 4, y < 0 \\ \text{Se} \ x = 2 \ ou \ x = 4, y = 0 \\ \text{Se} \ 2 < x < 4, y > 0 \end{cases} \\\\\\ \text{Assim}, (2x - 8) \ (2 - x) > 0 \ \text{para} \ 2 < x < 4 \\\\ \boxed{\text{S} = \ ]2, 4[ \ \ ou \ \ \text{S} = \{x \in \mathbb{R} \ | \ 2 < x < 4\}}

----------------------------------------------------------------------------------------------

Gráfico anexo abaixo.

• Azul: inequação do enunciado
(2x - 8) (2 - x) > 0 ou -2x² + 12x - 16 > 0

• Preto: função quadrática da inequação
f(x) = (2x - 8) (2 - x) ou f(x) = -2x² + 12x - 16